The Latest Medical Devices Used in the Field of Medicine - Sahib Jaber, Muhammad; obaid, Mohammad mohsen; Mahmoud, Mohammed Raad; Abed, Mustafa Kadhim (American Journal of Botany and Bioengineering, 2024)
Have you ever thought about how medical care is delivered? What factors are taken into account before administering treatment or prescribing medications? Progress in the medical device industry has indeed opened up a whole new dimension to personalized health care and improved patient outcomes in the medical field. Initially, the medical device industry was niche with humble beginnings until regulatory guidance was released outlining the general regulatory and quality system requirements that the manufacturers needed to adhere to. In the latest medical devices, which is the area of interest today, wireless technology, sensor technology, indicator lights, and others were added in order to update the old ones. The transformation of the healthcare workplace utilizing medical devices for better healthcare applications has brought many advantages to today’s healthcare sector. Medical devices can now be bought from the market with the latest software support. The low energy technology has one advantage, which is that it uses less power. It has been designed in such a way that it can be powered by an electronic battery. The numerical increase in medical devices required innovation and equally proficient experts who are seamlessly amalgamating medical science with technology. With the growing interdependence of medicine, machine learning, and computer science, several newer medical devices have been conceptualized. Branded equipment showcases defining changes in the domain of new medical devices catering to global hospital and home users. The industry is witnessing a shift from traditional diagnosis and treatments to preventive healthcare using artificial intelligence, IoT, and robotics. The continual evolution of medical devices into the technological domain and focus on the growing interaction and interdependence between medicine and medical devices has made a robust impact on the world.